21st century investing : redirecting financial strategies to drive systems change - Burckart, William; Lydenberg, Steven D. (Oakland : Berrett-Koehler Publishers, 2021)
Two experienced and visionary authors show how institutions and individuals can go beyond conventional and sustainable investing to address complex problems such as income inequality and climate change on a deep, systemic level.
Introduction : Theres No Time to Lose -- Chapter 1. Set Goals -- Chapter 2. Decide Where to Focus -- Chapter 3. Allocate Assets -- Chapter 4. Apply Investment Tools -- Chapter 5. Leverage Advanced Techniques -- Chapter 6. Evaluate Results -- Chapter 7. Case Example Investing to Address Income Inequality -- Chapter 8. Investors in Transition - Conclusion: The Time to Act Is Now.
Includes bibliographical references and index.
Keywords: Investments; Stocks; Social responsibility of business